The influence of the arts and the humanities on ‘personal skills’ among medical students and doctors: a scoping review - Pathiyil Ravi Shankar (Janaki Medical College Journal of Medical Science, 2024)
Medical humanities programs are offered at several medical schools. Workshops and sessions on the arts are also offered. The author examined studies from the literature to evaluate the evidence for the influence of the medical humanities on ambiguity and uncertainty, communication skills, empathy, observation skills, resilience and self-care either alone or in combination. Original research studies published between January 2000 to June 2024 in English language among premedical, medical students (preclinical and clinical), interns and residents were examined. PubMed and the Google Scholar databases were searched using the key words ‘Empathy’, ‘Tolerance of ambiguity’, ‘Wellbeing’, ‘Uncertainty’, ‘Observation skills’, ‘Resilience and self-care’, ‘Communication skills’, ‘Medical humanities’ and ‘Health humanities’. The abstract of the retrieved articles was carefully read through to examine if they explored the impact of the humanities module on one or more of the characteristics mentioned either quantitatively and/or qualitatively. If the abstract was deemed suitable to the study, the full text of the article was obtained and carefully read through. Duplicates were removed manually. A total of 52 articles were included. Twenty-seven studies (51.9%) focused on empathy either alone or with other characteristics and 25 studies described interventions among basic science medical students. More studies were quantitative, and 30 studies (57.7%) were from the United States. Most measured the studied parameters before and after the intervention using a validated checklist. The evidence for influence is strong for empathy and visual observation skills. There is also moderate evidence for resilience and well-being. The arts and the humanities can create ‘better’ doctors. More studies from developing countries are required.